Respuestas
Respuesta dada por:
3
Resolución :
-----------------------------------------------------------------------
1.-) ( 3 )( -12 ) = -36
2.-) ( 4 )( -12 ) = -48
Espero q te ayude!!!!!!!!!!!!!!!!
-----------------------------------------------------------------------
1.-) ( 3 )( -12 ) = -36
2.-) ( 4 )( -12 ) = -48
Espero q te ayude!!!!!!!!!!!!!!!!
glenda86salvatpahc7o:
muchas gracias
Respuesta dada por:
2
el triple:
![3 \times ( - 12) = - 36 3 \times ( - 12) = - 36](https://tex.z-dn.net/?f=3+%5Ctimes+%28+-+12%29+%3D++-+36)
el cuádruple:
![4 \times ( - 12) = - 48 4 \times ( - 12) = - 48](https://tex.z-dn.net/?f=4+%5Ctimes+%28+-+12%29+%3D++-+48)
espero haberte ayudado
el cuádruple:
espero haberte ayudado
Preguntas similares
hace 6 años
hace 6 años
hace 9 años
hace 9 años